2020
DOI: 10.1101/2020.12.08.415554
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A protease-initiated model of wound detection

Abstract: Wounds trigger surrounding cells to initiate repair, but it is unclear how cells detect wounds. The first known wound response of epithelial cells is a dramatic increase in cytosolic calcium, which occurs within seconds, but it is not known what initiates this calcium response. Specifically, is there an instructive signal detected by cells surrounding wounds? Here we identify a signal transduction pathway in epithelial cells initiated by the G-protein coupled receptor Methuselah-like 10 (Mthl10) activated arou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
(60 reference statements)
2
0
0
Order By: Relevance
“…These results are consistent with previous reports of Ca 2+ spikes being observed in discs that have reached their final size, and Ca 2+ waves being observed in smaller developing discs [19]. A recent study found that Ca 2 + signals are initiated in response to wounding by the G-protein coupled receptor Methuselah like 10 (Mthl10) [60]. Mthl10 is activated by Growth-blocking peptides (Gbps) [60].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with previous reports of Ca 2+ spikes being observed in discs that have reached their final size, and Ca 2+ waves being observed in smaller developing discs [19]. A recent study found that Ca 2 + signals are initiated in response to wounding by the G-protein coupled receptor Methuselah like 10 (Mthl10) [60]. Mthl10 is activated by Growth-blocking peptides (Gbps) [60].…”
Section: Discussionsupporting
confidence: 92%
“…A recent study found that Ca 2 + signals are initiated in response to wounding by the G-protein coupled receptor Methuselah like 10 (Mthl10) [60]. Mthl10 is activated by Growth-blocking peptides (Gbps) [60]. Whether Mthl10 also is involved in developmental growth requires further investigation, but may be consistent with our findings that intercellular calcium wave activity inhibits organ growth.…”
Section: Discussionsupporting
confidence: 89%